Co-occurrence of targetable mutations in Non-small cell lung cancer (NSCLC) patients harboring MAP2K1 mutations. (June 2020) - Scheffler, Matthias; Holzem, Alessandra; Kron, Anna; Nogova, Lucia; Ihle, Michaela A.; von Levetzow, Cornelia; Fassunke, Jana; Wömpner, Claudia; Bitter, Elisabeth; Koleczko, Sophia; Abdulla, Diana S.Y.; Michels, Sebastian; et al.
Highlights: MAP2K1 mutations are rare genomic events in NSCLC. They occur in both adenocarcinoma and squamous-cell carcinoma histology. They are rarely exclusive, co-occurring with potentially targetable coaberrations. Comprehensive multiplex sequencing at baseline is needed for detection. Further analyses will investigate the use of MEK-inhibitors in these patients. Abstract: Background: MAP2K1 mutations are rare in non-small cell lung cancer (NSCLC) and considered to be mutually exclusive from known driver mutations. Activation of the MEK1-cascade is considered pivotal in resistance to targeted therapy approaches, and MAP2K1 K57 N mutation could be linked to resistance in preclinical models. We set out this study to detect MAP2K1 mutations and potentially targetable co-mutations using a molecular multiplex approach. Methods: Between 2012 and 2018, we routinely analyzed 14.512 NSCLC patients with two next-generation sequencing (NGS) panels. In a subset of patients, fluorescence in-situ hybridization was performed to detect rearrangements or amplifications. We assessed clinical parameters and co-occurring mutations and compared treatment outcomes of different forms of systemic therapy. Results: We identified 66 (0.5%) patients with MAP2K1 mutations. Both adenocarcinoma (n = 62) and squamous cell carcinoma (n = 4) histology. The presence of the mutations was linked to smoking, and transversions were more common than transitions. K57 N was the most frequent MAP2K1 mutation (n = 25). Additional mutations were found in 57 patients (86.4%). Mutations of TP53 were detected in 33 patients, followed by KEAP1 mutations in 28.1%. 24 patients (36.4%) had either MAP2K1 -only or a co-occurring aberration considered targetable, including EGFR mutations, a BRAF V600E mutation and ROS1 rearrangements. Outcome analyses revealed a trend toward benefit from pemetrexed treatment. Conclusion: Our analysis shows that MAP2K1- mutated NSCLC patients might frequently present with potentially targetable aberrations. Their role in providing resistance in these subtypes and the possible therapeutic opportunities justify further analyses of this rare NSCLC subgroup.